Genetic Variation at IFNL4 Influences Extrahepatic Interferon-Stimulated Gene Expression in Chronic HCV Patients. (20th November 2017) - Rosenberg, Brad R; Freije, Catherine A; Imanaka, Naoko; Chen, Spencer T; Eitson, Jennifer L; Caron, Rachel; Uhl, Skyler A; Zeremski, Marija; Talal, Andrew; Jacobson, Ira M; Rice, Charles M; Schoggins, John W
Abstract : In chronic hepatitis C virus (HCV) infection, IFNL4 genetic variation influences hepatic interferon-stimulated gene (ISG) expression. Here, RNA sequencing analysis demonstrated that clinically unfavorable IFNL4 polymorphisms are associated with elevated ISG expression by peripheral blood mononuclear cells in chronic HCV. Abstract: Polymorphisms at IFNL4 strongly influence spontaneous resolution and interferon therapeutic response in hepatitis C virus (HCV) infection. In chronic HCV, unfavorable alleles are associated with elevated interferon (IFN)-stimulated gene (ISG) expression in the liver, but extrahepatic effects are less well characterized. We used RNA sequencing (RNA-Seq) to examine whether IFNL4 genetic variation ( rs368234815 ) modulates ISG expression in peripheral blood mononuclear cells (PBMC) during chronic HCV infection. ISG expression was elevated in unstimulated PBMC homozygous for the unfavorable ΔG IFNL4 variant; expression following IFN-α stimulation was comparable across genotypes. These findings suggest that lambda interferons may have broader systemic effects during HCV infection.